2020
DOI: 10.3390/antibiotics10010029
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside 6′-N-acetyltransferase Type Ib [AAC(6′)-Ib]-Mediated Aminoglycoside Resistance: Phenotypic Conversion to Susceptibility by Silver Ions

Abstract: Clinical resistance to amikacin and other aminoglycosides is usually due to the enzymatic acetylation of the antimicrobial molecule. A ubiquitous resistance enzyme among Gram-negatives is the aminoglycoside 6′-N-acetyltransferase type Ib [AAC(6′)-Ib], which catalyzes acetylation using acetyl-CoA as a donor substrate. Therapies that combine the antibiotic and an inhibitor of the inactivation reaction could be an alternative to treat infections caused by resistant bacteria. We previously observed that metal ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 51 publications
(81 reference statements)
2
16
0
Order By: Relevance
“…Following the steps of previous work indicating that selected metal ions interfere with the acetylation reaction [26-29, 31, 43, 44], we tested the effect of Ag 1+ . We chose this ion because, unlike other metals, ionophores were not necessary to observe reversion of resistance in growing bacterial cells when tested as an inhibitor of resistance to aminoglycosides mediated by AAC(6')-Ib [31]. Plazomicin was readily acetylated in vitro in a soluble extract of cells containing a recombinant clone harboring aac(2')-Ia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the steps of previous work indicating that selected metal ions interfere with the acetylation reaction [26-29, 31, 43, 44], we tested the effect of Ag 1+ . We chose this ion because, unlike other metals, ionophores were not necessary to observe reversion of resistance in growing bacterial cells when tested as an inhibitor of resistance to aminoglycosides mediated by AAC(6')-Ib [31]. Plazomicin was readily acetylated in vitro in a soluble extract of cells containing a recombinant clone harboring aac(2')-Ia.…”
Section: Discussionmentioning
confidence: 99%
“…These stumbling blocks warrant exploring alternative strategies such as the development of inhibitors of the enzymatic inactivation that together with the aminoglycoside form a combination therapy effective against resistant pathogens [13]. The recent finding that metal ions, some of them in complex with ionophores, inhibit the AAC(6′)-Ib-catalyzed acetylation of aminoglycosides and induce a reduction in the minimal inhibitory concentration (MIC) of amikacin to susceptibility levels proved this concept and increased expectations that multidrug resistant infections could be treated by these combination therapies [26][27][28][29][30][31]. In particular, Ag 1+ inhibits the acetylation of amikacin by AAC(6′)-Ib and reverses resistance in bacteria in culture at low concentrations without needing an ionophore [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amikacin is an aminoglycoside most commonly administered intravenously and intramuscularly, yet other routes are also utilized, such as intrathecal, intraventricular, topical, and inhaled 8 , 17 , 18 . In our quest to identify compounds that inhibit the AAC(6′)-Ib amikacin-disabling action, we recently found that various cations effectively interfere with the enzymatic inactivation 11 , 12 , 19 21 . In the case of Zn 2+ , the concentrations needed to inhibit growth of amikacin-resistant cells in the presence of the antibiotic are significantly reduced if the cation is added to the growth media in complex with ionophores 11 13 , 20 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Amikacin is an aminoglycoside most commonly administered intravenously and intramuscularly, yet other routes are also utilized, such as intrathecal, intraventricular, topical, and inhaled 8,17,18 . In our quest to identify compounds that inhibit the AAC(6′)-Ib amikacin-disabling action, we recently found that various cations effectively interfere with the enzymatic inactivation 11,12,[19][20][21] . In the case of Zn 2+ , the concentrations needed to inhibit growth of amikacin-resistant cells in the presence of the antibiotic are significantly reduced if the cation is added to the growth media in complex with ionophores [11][12][13][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%